27‐4: Material and Design Optimization to Improve Color Performance of Automobile Displays1. Issue 1 (17th July 2018) - Shi, Bo; Zuo, Xiongcan; Xue, Rui; Yen, Kuochang; Qi, Xiaojing; Zhang, Junrui; Jiang, Ni; Feng, Yuanming
Abstract : Automobile displays require special color performance, such as dominant wavelengths (λdom ) of red, green, and blue (RGB), saturation levels (Sat) of RGB, and white (W) coordinates. In this paper, the authors optimize color filter (CF) resin, backlight unit (BLU), and design parameters for a liquid‐crystal display (LCD) in order to improve color performance without white calibration.